G559(P) Family oriented variable and its impact on clinical practice. (25th October 2020) - Saxena, V; Tammali, M; Mittal, S; Jain, K
Abstract : Aim: To assess the clinical, parental involvement and economic impact of the weaning methods of oxyen in LTOT. Methodology: Retrospective review of clinical records of babies discharged between Jan 2014 and Dec 2015 were compared to babies discharged between Jan 2016 to Dec 2017. Old protocol, weaning done in increments of 30 min, 1 hr, 2 hr, 3 hr twice daily off, 6 hr, 8 hr, 10 hr off with an OOS at each step. New protocol, general health and nutritional status guide the daytime O2 weaning. Weaning done in increments of 30 min, 2 hr twice daily off, 6 hr and 12 hr off in day time followed 2–3 weeks later by two OOS, one in oxygen and one in air. Results: 33 babies were discharged each year on LTOT. Groups were comparable in mean birth weight (kg), gestational age and comorbidities (table 1 ). New protocol was associated with shorter duration of O2 therapy (P value0.005). There was saving of £3215.54 for cost of oxygen in 2016–17. The parent satisfaction and the Friends and Family test score were 100%. Conclusions: Structured monitoring and weaning based on clinical parameters and parental input led to shorter duration of LTOT The service users' feedback was 100% positive. Not all activities to provide this service were coded.